2017
DOI: 10.1139/apnm-2016-0701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise-induced dehydration on circulatory markers of oxidative damage and antioxidant capacity

Abstract: Dehydration is a common event associated with exercise. However, few studies have examined the effects of dehydration on plasma redox status in humans. Eighty-two athletes were recruited and had Baseline anthropometrics and blood samples obtained. Athletes then engaged in a dehydration protocol, training until 3% of pre-weight body mass was lost. Athletes returned to the lab and had Post-dehydration blood collected. Athletes then consumed an isotonic drink until pre-exercise body weight was reestablished. Bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…258-265. doi:10.1111/j.1553-2712.1998.tb02624.x. Georgescu, V.P., de Souza Junior, T.P., Behrens, C., Barros, M.P., Bueno, C.A., Utter, A.C., et al 2017. Effect of exercise-induced dehydration on circulatory markers of oxidative damage and antioxidant capacity.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…258-265. doi:10.1111/j.1553-2712.1998.tb02624.x. Georgescu, V.P., de Souza Junior, T.P., Behrens, C., Barros, M.P., Bueno, C.A., Utter, A.C., et al 2017. Effect of exercise-induced dehydration on circulatory markers of oxidative damage and antioxidant capacity.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…
We read with great interest a recent article by Georgescu et al (2017) entitled "Effect of exercise-induced dehydration on circulatory markers of oxidative damage and antioxidant capacity". The authors aimed to investigate effects of hydration and rehydration by using sensitive indirect measures of oxidative stress and the antioxidant capacity response.
…”
mentioning
confidence: 99%
“…Many studies have reported the consequences of dehydration on physical and mental levels, highlighting humoral changes and cognitive deficits, which not only compromise normal daily activities but can negatively affect sports performance [4][5][6]. More specifically, it has been shown that the inadequate restoration of fluids during exercise compromises neuromuscular function, increases fatigue perception, reduces technical skills, affecting metabolic and autonomic nervous system parameters [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of maintaining a euhydrated state, studies have shown individuals are not adequately replacing fluid during exercise [21]. Although many studies have investigated the physiological responses to dehydration [4][5][6][7][8][9][10][11][12], to our knowledge, no research has evaluated the impact of dehydration on both metabolic and neuromuscular variables during performance in active males. Therefore, the purpose of our study was to investigate the effects of progressive dehydration on heart rate (HR), oxygen uptake (VO 2 ), energetic cost, and neuromuscular functionality during both submaximal cycling exercise at a constant work rate and subsequent time-to-trial (TT) performance.…”
Section: Introductionmentioning
confidence: 99%
“…Heat stress and dehydration independently can disrupt this balance [40][41][42]. Heat stress can disrupt this balance through excessive metabolic ROS production and lowered antioxidant activity, resulting in a state of oxidative stress [43,44].…”
Section: Introductionmentioning
confidence: 99%